1977
DOI: 10.1111/j.1744-7348.1977.tb01800.x
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary glasshouse and field tests of soil partial sterilants for clubroot control

Abstract: Experiments were made on field plots and in individually dosed pots to investigate the effects of ten soil partial sterilants on percentage infection of cabbage with clubroot. Additionally, cores of naturally-infested soil or samples of artificially infested and buried soil removed from some treated plots were also sown with cabbage in a glasshouse and the seedlings then assayed for the presence of clubroot. There was evidence that the partial sterilants were optimally effective at different depths. Dowfume M.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1977
1977
2014
2014

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 3 publications
0
15
0
Order By: Relevance
“…Metham sodium prevented infection and symptom expression at half the recommended field dose and showed activity down to one eighth the field dose. However, past experience with methyl isothiocyanate generators (Buczacki and White, 1977) suggested that the downward penetration of the gas would be insuflicient to give complete or lasting control of a soil-borne disease in the field. Metham sodium at 1 or 2 X field dose was phytotoxic even though a cress test had indicated absence of residual methyl isothiocyanate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Metham sodium prevented infection and symptom expression at half the recommended field dose and showed activity down to one eighth the field dose. However, past experience with methyl isothiocyanate generators (Buczacki and White, 1977) suggested that the downward penetration of the gas would be insuflicient to give complete or lasting control of a soil-borne disease in the field. Metham sodium at 1 or 2 X field dose was phytotoxic even though a cress test had indicated absence of residual methyl isothiocyanate.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the control of clubroot disease {Plasmodiophora brassicae Wor.) by soil sterilisation (Buczacki and White, 1977) showed that although the results of small scale tests tended to over-estimate the efficacy of treatments, tests based on decreasing dosages to a quarter or an eighth of the field dose tacihtated the selection of the most active chemicals.…”
Section: Laboratory Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…After a cress test (Buczacki and White, 1977) to confirm the absence of phytotoxic residues, seeds were drilled on 31 May at 15-cm spacing in rows 30 cm apart. At harvest on 23 October, 50 plants were taken at random from each plot and the head weights and numbers with clubroot symptoms were recorded.…”
Section: Control Of Clubroot By Soil Sterilants 37mentioning
confidence: 99%
“…Previous accounts (Buczacki and White, 1977;White and Buczacki, 1977b) described the use of soil sterilants including dazomet and 1, 3-dichloropropene for the eradication of small infestation foci of the clubroot causal organism, Plasmodiophora brassicae Wor. In those studies the treatment cost, although large, was considered to be unimportant when weighed against the possibility of preventing the spread of the disease from the infested areas to uncontaminated land.…”
Section: Introductionmentioning
confidence: 99%